Modelo multicritério construtivista para avaliação de desempenho em compras públicas: estudo de caso na UTFPR-Câmpus Pato Branco - Lindner, Ana Paula (2018)
Public institutions, in general, face difficulties in carrying out the organizational performance assessment of public purchases. Therefore, the present research aimed to develop a constructivist performance evaluation model for the Purchasing Division of the Federal Technological University of Paraná - Pato Branco Campus. To achieve the purpose, it was first conducted a systematic review of the literature using ProKnow-C intervention instrument. Subsequently, the Methodology Multicriteria Decision Aid – Constructivist (MCDA-C) intervention instrument was used, with the purpose of developing the performance evaluation model for the Purchasing Division of UTFPR- Pato Branco Campus. The systematic review of the literature pointed to several gaps, such as: (i) the proposed performance evaluation models are not unique to the decision context; (ii) the models developed do not allow the construction of knowledge in the decision-maker of the decision-making context; (iii) the measurement performed does not allow the integration of the evaluation criteria; and, (iv) the models developed do not allow to generate improvement actions. The main results of the constructed model are: (i) 30 primary elements of evaluation; (ii) 85 action-oriented concepts; (iii) two major dimensions were identified as areas of concern for decision makers, Management and Planning; (iv) six cognitive maps have been developed to better understand decision-making objectives; (v) 53 performance indicators were constructed; and, (vi) several actions have been generated to improve the performance of the Purchasing Division. From the comparison of the literature with the constructed model, it was possible to conclude that few indicators found in the literature had some similarity with the indicators of the developed model, being that this allows to conclude on the necessity of the models to be singular. It was possible to conclude the present work filled some gaps identified in the literature, such as: (i) to propose a unique performance evaluation model to the decision maker and the context; (ii) to propose a model in which it was concerned to generate knowledge in the decision maker; (iii) to propose a model in which the measurement made possible the criteria integration; and, (iv) to propose a model that allowed to generate improvement actions.